Developing Whiteboard Animation as an Educational Media for Electronic Waste Management in the Special Region of Yogyakarta (DIY) - Arif Ranu Wicaksono (Institut Seni Indonesia Denpasar, 2024)
The Electronic waste is included in the B3 (hazardous and toxic materials) waste category, requiring special handling. Based on statistical data from the Independent Waste Management Information System website managed by the Environment and Forestry Service (DLHK) of the Special Region of Yogyakarta, the daily electronic waste collected is around 78 kg. Of the 78kg of electronic waste, 48kg can be processed, consisting of 45kg of electronic waste and 30kg of used battery waste, leaving the remaining 3kg as residue. Yogyakarta City's electronic waste is expected to grow year after year, meaning that a solution is required. One of the solutions is to provide communicative and easy-to-understand educational media to the public, with a broad impact on the residents of Yogyakarta City, so that, electronic waste can be managed effectively in the future, with the hope of reducing the negative impact of environmental pollution on land, water sources, and air. Educational media about electronic waste is still limited, and residents of Yogyakarta City remain unaware of the issue, as evidenced by the fact that when disposing of electronic waste, they mix organic and inorganic waste. Researchers developed an animated video using the Whiteboard application as an educational media for electronic waste management in Yogyakarta. The Whiteboard animation video was developed using the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation). It is expected that this media design will increase the awareness of Yogyakarta City residents of proper electronic waste management practices.